Modification of shapley value and its implementation in decision making - Leszek Zaremba; Cezary S. Zaremba; Marek Suchenek (Foundations of Management, 2017)
The article presents a solution of a problem that is critical from a practical point of view: how to share a higher than usual discount of 10 million among 5 importers. The discount is a result of forming a coalition by 5 current, formerly competing, importers. The use of Shapley value as a concept for co-operative games yielded a solution that was satisfactory for 4 lesser importers and not satisfactory for the biggest importer. Appropriate modification of Shapley value presented in this article allowed to identify appropriate distribution of the saved purchase amount, which according to each player accurately reflects their actual strength and position on the importer market. A computer program was used in order to make appropriate calculations for 325 permutations of all possible coalitions. In the last chapter of this paper, we recognize the lasting contributions of Lloyd Shapley to the cooperative game theory, commemorating his recent (March 12, 2016) descent from this world.
Keywords: 650; characteristic function; coalition; cooperative game; core of game; imputation; Shapley value